Pengaruh Work Environment dan Perceived Organizational Support terhadap Employee Engagement pada Karyawan Kantor POS Kabupaten Tuban - Meidytania, Vinolia Putri; Frianto, Agus (Jurnal Ilmu Manajemen, 2024)
This study investigated the impact of work environment and perceived organisational support on employee engagement. The data was analysed using a multiple linear regression technique using the SPSS 25 version. The sample came from employees of the expedition company in Tuban, with a total of 40 respondents using the saturated sample technique. The statistical result showed that the work environment has a positive significant effect on employee engagement. A good work environment can make employees more comfortable and increase their engagement. In the same way, perceived organisational support also has a significant positive impact on employee engagement. Good support from the company can trigger employee enthusiasm and increase employee engagement. In addition, the test results demonstrated that employee engagement is positive and significantly impacted by the work environment and perceived organisational support. Based on the research results, companies need to maximise the quality of the work environment further, both physically and socially, and maximise support, such as being more responsive to complaints and reinforcing regulations that can equalise the treatment of each employee, increasing employee engagement.